Wykonywanie zadań o charakterze użyteczności publicznej przez jednostki samorządu terytorialnego a działalność gospodarcza - Gola, Jan (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The article presents arguments qualifying activities undertaken by local government units for public benefit as an economic activity. After studying the definition of public utility it was indicated that — basing on the Polish courts judicature — local government may be regarded as an entrepreneur conducting economic activity only within its own scope of tasks and only if they are related to engagement in the economic turnover. An issue of profit has been addressed, being considered as asecondary and supporting category. Title activity is characterized by specific legal regime, so as supporting function in the context of performance of the basic tasks of local government units.
Keywords: jednostki samorządu terytorialnego; działalność gospodarcza; zadania o charakterze użyteczności publicznej